Cosmopolitan paradox dynamic egalitarianism in the redevelopment of the Cultural Center of the Philippines complex - Morallos, Chris Jehram M.; Gines, Leonido Jr. M. (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
The Cultural Center of the Philippines (CCP) Complex stands as a testament to Filipino
cultural identity, yet it faces mounting challenges, including governance inefficiencies,
commercialization, and physical decline. The non-implementation of the 2003 master
plan and the persistence of the Edifice Complex have hindered its ability to evolve as
an inclusive cultural space. This study critically examines how architectural
monumentalism, centralized governance, and global-local tensions have shaped the
complex's trajectory and explores strategies for its adaptive redevelopment.
Employing a mixed-methods approach, including archival research, stakeholder
interviews, surveys, and spatial assessments-this research evaluates the CCP's
architectural, cultural, and institutional landscapes. Findings reveal that
monumentalism and state-driven narratives have marginalized participatory
governance, limiting the complex's engagement with contemporary cultural dynamics.
In response, the study introduces Symbiotic Pluralism, a framework integrating
UNESCO's Historic Urban Landscape (HUL) principles, participatory governance,
and sustainable urban strategies. By reconciling heritage conservation with inclusive
modernization, the CCP can reassert its role as a living cultural institution that bridges
historical legacy and contemporary Filipino identity. This study underscores the
imperative for responsive, community-driven policies to sustain the CCP as a dynamic,
relevant, and accessible cultural hub.
Include appendices
Thesis (Master of Architecture) -- University of the Philippines Diliman
Keywords: Cultural Center of the Philippines; Cultural landscapes; Sustainable development; Cultural landscapes -- Preservation; Equality; Urban renewal